Sharing the Dragon's Teeth Terrorist Groups and the Exchange of New Technologies - Cragin, Kim (RAND Corporation, 2007)
Case studies of 11 terrorist groups in Mindanao, the West Bank and Gaza Strip, and southwest Colombia show how these groups have exchanged technologies and knowledge in an effort to innovate (i.e., improve their operational capabilities). The analysis provides national security policymakers with insight into the innovation process and suggests ways that government policies can create barriers to terrorists' adoption of new technologies.